Measuring the impact of strategic vigilance reflection on innovative marketing: Research edited by a sample of employees of the Iraqi cmompany for the manufacture and marketing of dates (mixed contribution) (Entrepreneurship Journal for Finance and Business, 2020)
The organizations are interested in adopting everything that includes the upgrading of strategy and strategy planning processes to develop marketing processes, as it enables the organization to delve into new horizons that increase its competing potential and its marketing capabilities, so the established systems need to Distinguished management leaders are able to better adapt to environmental change, as they help the organization achieve many mutually friendly advantages.The research studies two different actors with each other to be the creative framework for research, both of which are (strategic vigilance, innovative marketing), where research ensures its theoretical and practical aspects are comprehensive coverage of the problem, as the search enables the use of the best possible Available from theoretical information in scientific sources available from a very well-known, and to make sure that research hypotheses can be accepted through analysis and interpretation of the diagnosis of correlation and influence between its variables from another side, as the faith uses the method of intentional sample to obtain data The required questionnaire prepared for this purpose, based on statistical methods for the analysis of those data provided by the statistical program (SPSS V.18), according to the exploratory approach to the analysis of the problem.The researcher concluded that there are correlations to the amount of ( 0.188 ) and impact relationships of ( 93.51 ) between research variables ( strategic vigilance, innovative marketing ), for the target sample of the number ( 30 ) seen, where a number of conclusions were marked the most important ownership of the company ( The target is a database that suffers from the tin of reliable technological methods, or is not available to all employees of the company, in addition to having technology that is not very advanced or is not approved to provide new products ), as well as to make recommendations for a return from The most important ones ( the need to find an electronic database using modern technical methods that all workers can access, access and evaluate their information).